Bibliometric and visual analysis in the field of electroacupuncture’s analgesia and regulation on negative emotion from 2014 to 2024 - Huang, Xubo; Gao, Jiajie; Ding, Yuxin; Wang, Jiali; Fang, Junfan; Fang, Jianqiao; Du, Junying (Frontiers in Neurology, 2025)
IntroductionThis bibliometric study systematically analyzes the research landscape of electroacupuncture (EA), focusing on its applications in pain relief and emotional regulation from 2014 to 2024. EA, a contemporary adaptation of traditional acupuncture, has gained significant attention for its potential therapeutic benefits in managing chronic pain and mood disorders.MethodsUsing the Web of Science Core Collection as the primary data source, we identified 537 articles related to EA’s therapeutic effects. The analysis was conducted using bibliometric tools such as VOSviewer and CiteSpace to visualize publication trends, research hotspots, and collaborative networks.ResultsThe study highlights a significant upward trend in research output, with a marked increase in publications from 2019 onwards. China emerged as the leading contributor, accounting for over 60% of the total research output, followed by the United States and South Korea. Key institutions, such as Zhejiang Chinese Medical University and Shanghai University of Traditional Chinese Medicine, have made substantial contributions, emphasizing the importance of traditional Chinese medicine in this research area. Major research themes include the modulation of neurotransmitter systems, the role of endogenous opioids, and the impact of EA on chronic pain and mood disorders. Collaborative networks between countries and institutions are mapped, revealing the centrality of Chinese and American research partnerships.DiscussionThis comprehensive analysis outlines the current state of EA research and identifies gaps and opportunities for future studies, particularly in understanding the mechanistic pathways of EA and its integration into mainstream medical practices. The findings provide a roadmap for enhancing the therapeutic applications of EA and underscore its potential in managing complex conditions involving both physical and emotional components.